The Costs of Urban Sprawl - Predicting Transport Greenhouse Gases from Urban Form Parameters - Trubka, Roman; Newman, Peter; Bilsborough, D. (Royal Australian Institute of Architects, 2010)
This is one of three companion papers taken from a study that assesses the comparative costs of urban redevelopment with the costs of greenfield development. The first paper, GEN 83: The Costs of Urban Sprawl – Infrastructure and Transportation, showed that substantial costs would be saved in infrastructure and transport if urban redevelopment were the focus. This paper assesses how these different urban typologies perform with respect to greenhouse gases. The final paper GEN 85: The Costs of Urban Sprawl – Physical Activity Links to Healthcare Costs and Productivity discusses the health costs and productivity losses that can be linked to human inactivity in suburban living.The redevelopment option in Australian cities is around 4.4 tonnes less greenhouse gas intensive per household per annum than greenfield development. The study shows how greenhouse gases can be calculated for any development based on simple physical planning parameters such as the distance to the CBD (a reflection of distance travelled and a proxy for density) and transit accessibility. Although the actual costs of greenhouse gas are small the significance of this work is that governments will need to demonstrate how they are reducing climate change impacts and thus greenfields developments will find it hard to pass this fundamental criteria of assessment.